Reference charts of birth weight and birth length by gestational age in south east Serbian newborns: Preliminary results - Stanković Sandra; Ignjatović Aleksandra; Vučić Jelena; Stanković Tatjana; Živić Saša; Manojlović Milena; Stanković Miodrag; Vorgučin Ivana (Vojnosanitetski Pregled)
Background/Aim. To date, there has been no population-based neonatal anthropometric chart published in Serbia. Charts based on infants born in a single hospital (hospital-based) in the 1 990s are still widely used in our country, as well as the Alexander chart. The aim of this study was to construct population-based centile, gender-specific charts for birth weight and length for singleton infants born in Southeast Serbia from 24 t o 42 weeks of gestation and to compare them with other previously published charts. Methods. Data on 39,842 singleton live infants, delivered from 2006 to 2015 in three maternity wards in Southeast Serbia (Niš, Prokuplje, and Aleksinac), were analyzed. Results. The inclusion criteria met 37,169 newborns. Preterm births were relatively uncommon (5.25%). Estimated centile charts for male and female birth weights and lengths were constructed showing the 3rd, 10th, 25th, 50th, 75th, 90th, and 97th centiles. Conclusion. Our birth weight percentiles provide a population norm for singleton infants adjusted for gender, born in Southeast Serbia. These references are both of epidemiological and clinical use. There is a need for large-scale research that will include a larger number of pre-term newborns which were represented in limited numbers in our study. There is also a need for setting up the gold standard method for the precise determination of the gestational age, i.e. the use of the early fetal ultrasound.